The Manager's Guide to Quick Crisis Response : Effective Action in an Emergency. - Blythe, Bruce T. (Rothstein Publishing, 2016)
Avoid being "blindsided" by an unexpected emergency or crisis in the workplace - violence, natural disaster, or worse! Bruce Blythe's The Manager's Guide to Quick Response in a Crisis: Effective Action in an Emergency offers the time-tested skills that prepare you to act effectively - on behalf of yourself and your co-workers - in the face of threat and chaos. Blythe uses real-world case studies, examples, and checklists to help you be the top-notch leader the situation requires